Հայերի տեղահանությունը Ադրբեջանից: 1988 թ. Կիրովաբադի հայերի ինքնապաշտպանության դասերը - Խառատյան, Հրանուշ (ԱրՊՀ հրատ․)
Процесс депортации армян в 1988-1990 гг. из Советского Азербайджана происходил при совместных согласованных действиях властей и социально низких слоев азербайджанского общества, с попустительства высших структур власти СССР, в условиях информационной блокады. В статье рассматриваются случаи силовой депортации армян из сел Знаберд, Нахичевана, Бананц и Кушчи Дашкесанского, Кйалбанд и Галага Исмайилинского районов, городов Шаки и Кировабада, организация самообороны армян Кировабада от 21 ноября по 14 декабря, которое повлияло на тактику властей по депортации армян и нзменило ход событий. The process of expelling and dislocation of Armenians from the Soviet Azerbaijan during 1988-1990 was carried out through mutually agreed actions of the authorities and lower social classes of Azerbaijani society, with a permission from the highest USSR authorities and in an informational blockade. The article examines the cases of forcible displacement of Armenians from Znaberd village of Nakhijevan, Banants and Kushchi villages of Dashkesan, Qyalband and Ghalaga villages of Ismaili region, and the cities of Shaki and Kirovabad. It also reviews the organization of self-defense of Kirovabad Armenians from November 21 to December 14 of 1988, which had an impact on the tactics of the authorities with respect to the displacement of Armenians.
Keywords: Հայոց ցեղասպանություն; Արցախ